Thermoelectric Materials: Thermoelectric Properties of Novel Semimetals: A Case Study of YbMnSb2 (Adv. Mater. 7/2021). Issue 7 (16th February 2021) - Pan, Yu; Fan, Feng‐Ren; Hong, Xiaochen; He, Bin; Le, Congcong; Schnelle, Walter; He, Yangkun; Imasato, Kazuki; Borrmann, Horst; Hess, Christian; Büchner, Bernd; Sun, Yan; et al.
Abstract : In article number 2003168, Yu Pan, Chenguang Fu, Claudia Felser, and co‐workers investigate the thermoelectric properties of a novel nodal line semimetal, YbMnSb2 . The Dirac bands guarantee high charge‐carrier mobility, and, simultaneously, a regular band provides a large density of states leading to a large thermopower. The power factor of single‐crystal YbMnSb2 is found to be competitive with conventional high‐performance thermoelectric semiconductors, even binary Bi2 Te3 single crystals.